The dancing body in Renaissance choreography : kinetic theatricality and social interaction - Franko, Mark (Anthem studies in theatre and performance., 2022)
The Dancing Body in Renaissance Choreography is a study of the theory of kinetic theatricality in the western European context. The dancing body of courtly social dance is analyzed in French and Italian dance treatises of the Renaissance through the intertexts of oratorical action, pedagogical discourses of civility and conceptions of value emanating from descriptions of social interaction in courtesy books.